2020
DOI: 10.30895/2312-7821-2020-8-1-9-22
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response Checkpoint Inhibitors: New Risks of a New Class of Antitumor Agents

Abstract: The introduction into clinical practice of immune checkpoint inhibitors that block cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), programmed cell death protein-1 (PD-1), and programmed cell death ligand-1 (PD-L1), has improved the prognosis of patients with malignant neoplasms of diff erent localisation. The antitumour eff ect of immune checkpoint inhibitors is based on blocking CTLA-4 and PD-1/PD-L1 signaling pathways and enhancing lymphocyte antitumour activity. However, inhibition of immune checkpoints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 108 publications
(181 reference statements)
0
5
0
Order By: Relevance
“…In the clinical case described by us, a hyperergic immune response can be observed, which led to the development of several irAEs with simultaneous manifestation. However, if in the case of vitiligo in melanoma we can talk about the formation of a good response to ICPI (a possible increase in the sensitivity of melanocytes [ 2 ]), and hence an increase in overall and relapse-free survival [ 11 ], the reason for the development of endocrine lesions is unclear. However, such vitilig-like depigmentation differs from classical vitiligo (the latter is localized in photo-exposed areas, and the Kebner phenomenon is observed) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the clinical case described by us, a hyperergic immune response can be observed, which led to the development of several irAEs with simultaneous manifestation. However, if in the case of vitiligo in melanoma we can talk about the formation of a good response to ICPI (a possible increase in the sensitivity of melanocytes [ 2 ]), and hence an increase in overall and relapse-free survival [ 11 ], the reason for the development of endocrine lesions is unclear. However, such vitilig-like depigmentation differs from classical vitiligo (the latter is localized in photo-exposed areas, and the Kebner phenomenon is observed) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, James P. Allison and Tasuku Honjo were awarded the Nobel Peace Prize in Medicine for their discovery of a fundamentally new approach in the treatment of malignant neoplasms [ 1 ]. The antitumor effect of this type of immunotherapy is realized through blocking the control signaling pathways CTLA-4 (cytotoxic T-lymphocyte-associated protein 4), PD-1 (programmed cell death-1 protein) and PD-L1 (programmed cell death receptor ligand-1), which leads to an increase in the antitumor activity of the immune system and is accompanied by an improvement in overall survival rates in a number of tumors [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COLCORONA study [158] reported that the use of colchicine in outpatients with COVID-19 reduced the risk of hospitalization by 25%, death by 44%, and the need for ventilation by 50%.…”
Section: Anti-cytokine Therapymentioning
confidence: 99%
“…Endocrine tissue does not regenerate and has a very small volume, so immune destruction has great consequences for the secretion of major hormones [5]. The development of clinically significant immune mediated adverse reactions may require discontinuing antitumor therapy and prescription of immunosuppressants, so early diagnosis and timely therapy of complications serve as important criteria for successful antitumor therapy [6].…”
Section: Introductionmentioning
confidence: 99%